2007
DOI: 10.3133/ofr20071040
|View full text |Cite
|
Sign up to set email alerts
|

Methods for Estimating Annual Wastewater Nutrient Loads in the Southeastern United States

Abstract: Multiply By To obtain Length mile (mi) 1.609 kilometer (km) Flow rate million gallons per day (MGD) 0.04381 cubic meters per second (m 3 /s) Note: The abbreviation MGD will be used in this report as an abbreviation for "million gallons per day" for consistency between the text in the body of the report and language used in the programs included in the attachments.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
26
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(26 citation statements)
references
References 0 publications
0
26
0
Order By: Relevance
“…To meet the need for reliable information on point‐source nutrient loads to surface waters, we present a methodology for systematically evaluating and, where possible, improving the quality of the PCS data for calculating annual loadings to U.S. streams. Our approach refines the previous methods employed by the USEPA (2006a,b) and McMahon et al. (2007) to address specific data needs to support recent model‐based assessments of nutrient sources in six major regional watersheds (called major river basins, or MRBs) (Figure 1) of the continental U.S.…”
Section: Introductionmentioning
confidence: 81%
See 4 more Smart Citations
“…To meet the need for reliable information on point‐source nutrient loads to surface waters, we present a methodology for systematically evaluating and, where possible, improving the quality of the PCS data for calculating annual loadings to U.S. streams. Our approach refines the previous methods employed by the USEPA (2006a,b) and McMahon et al. (2007) to address specific data needs to support recent model‐based assessments of nutrient sources in six major regional watersheds (called major river basins, or MRBs) (Figure 1) of the continental U.S.…”
Section: Introductionmentioning
confidence: 81%
“…The pilot project approach was based on procedures used in an USEPA investigation of nutrient loading to the Mississippi River basin (USEPA, 2006a,b). The methods and data developed in the pilot study for the Southeast (MRB2) were reported by McMahon et al. (2007) and by Hoos et al.…”
Section: Study Methodsmentioning
confidence: 99%
See 3 more Smart Citations